Railway expansion joint gaps and hooks detection using morphological processing, corner points and blobs - Islam, Samiul (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.